Parental Mentoring in Supporting Children’s Home Learning Activities in Percut Sei Tuan - Andi Suhendra Siregar (Rahis Cendekia Indonesia, 2025)
Parental involvement is a crucial factor in supporting children’s learning processes, particularly within the home environment where learning habits and character development are formed. However, many parents face challenges in effectively assisting their children due to limited pedagogical knowledge, time constraints, and lack of guidance on appropriate learning strategies. This community service program aimed to empower parents with the knowledge and skills needed to support their children’s learning activities at home. The program employed a participatory and educational approach involving parents of elementary school-aged children. The activities were conducted through needs assessment, educational workshops, group discussions, guided practice, and evaluation sessions. The materials focused on effective home-based learning strategies, time management, positive parent–child communication, and the creation of a conducive learning environment. Data were collected through observations, questionnaires, and participants’ reflections, and analyzed descriptively to evaluate the program’s outcomes. The results indicate that the parental assistance program positively influenced parents’ understanding, attitudes, and practices in supporting children’s learning. Parents demonstrated increased confidence in organizing learning schedules, assisting with assignments, and motivating their children through supportive and empathetic approaches. Additionally, parents reported improvements in children’s learning motivation, engagement, and adherence to study routines at home. Despite these positive outcomes, challenges related to parents’ time availability and diverse educational backgrounds were identified. These findings suggest the importance of flexible program design and continuous support to ensure sustainability. Overall, this community service initiative highlights the effectiveness of empowering parents as active partners in children’s education and contributes to the development of collaborative school–family relationships that enhance the quality of home-based learning